1986
DOI: 10.1007/bf01658645
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent varicose veins

Abstract: When Doppler ultrasound was introduced for the assessment of patients with varicose veins, a more accurate clinical appraisal of the pathophysiology of this condition became possible. In particular, it enabled identification of those patients with recurrent varicose veins who had had inappropriate or inadequate initial treatment. It facilitated planning of appropriate further treatment. The more widespread use of radiology, in particular varicography, as a means of preoperative assessment of recurrent varicose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 16 publications
1
56
0
3
Order By: Relevance
“…For example, varicose veins recur after surgery in 20-40 per cent of patients 98 . Recurrence was previously thought to be caused by poor surgical technique, especially when operations were performed by surgical trainees 99 , anatomical variability and complexity of the saphenofemoral junction 100 , and disease progression 101 . However, it is now believed that neovascularization reconnecting the venous channels is the probable cause of most recurrent disease 102,103 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, varicose veins recur after surgery in 20-40 per cent of patients 98 . Recurrence was previously thought to be caused by poor surgical technique, especially when operations were performed by surgical trainees 99 , anatomical variability and complexity of the saphenofemoral junction 100 , and disease progression 101 . However, it is now believed that neovascularization reconnecting the venous channels is the probable cause of most recurrent disease 102,103 .…”
Section: Discussionmentioning
confidence: 99%
“…Duplex scanning and hand-held Doppler are accurate for the identification of reflux sites (saphenofemoral and saphenopopliteal junctions) and recurrent disease [4][5][6][7][8][9][10][11][12][13][14]. Previous retrospective studies showed that traditional clinical examination alone was unreliable in assessing varicose veins and that Doppler and duplex are more reliable for the diagnosis of primary varicose veins [8,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…5 Various suggestions have been made for the cause of this high rate of recurrence, including poor surgical technique, particularly by junior surgeons in training 6 ; anatomic variability and complexity of the SFJ 7 ; and persistent progressive venous disease. 1 However, it is now believed that the most common cause of this recurrence is angiogenesis with new vessel formation and reconnection of the venous channels.…”
Section: Clinical Perspective P 74mentioning
confidence: 99%